A cost-of-illness study of eosinophilic esophagitis in Italy: assessing direct and indirect costs - Fortunato, Agostino; Antonini, Debora; Savarino, Edoardo Vincenzo; Racca, Francesca; Penagini, Roberto; Fanelli, Francesca; Saab, Jean Pierre; Cipriani, Filippo; Giodice, Roberta; Rumi, Filippo; Cicchetti, Americo (Frontiers in Gastroenterology, 2024)
BackgroundEosinophilic esophagitis (EoE) is a chronic and progressive type 2 inflammatory disease affecting the esophagus. Its prevalence has increased in recent years due to increased awareness, evolving clinical guidelines, and heightened sensitivity among healthcare professionals managing the condition. The exact causes behind EoE’s development remain unknown, and its clinical presentation varies, often leading to significant diagnostic delays depending on the age at which symptoms manifest. Consequently, achieving long-term disease control through heightened awareness becomes imperative. EoE generates a significant clinical burden, resulting in substantial economic consequences for patients, healthcare systems, and society. This study aimed to assess the economic and social impacts on EoE patients within the Italian context.MethodsA cost-of-illness analysis was conducted from two perspectives: the National Health System (NHS) and the societal perspective. This analysis encompassed direct healthcare, indirect healthcare, and non-healthcare costs. Data were collected and assessed through a survey administered to a panel of expert clinicians and EoE-affected patients.ResultsManaging EoE incurs a significant burden on healthcare systems, amounting to €6,852.28 per patient per year. The primary cost component appears to be direct costs, comprising 60.73% of the total cost per patient for this condition, while indirect costs contribute to 29.68% of the overall management expenses.ConclusionThis analysis underscores a substantial financial burden on both the healthcare system and patients affected by eosinophilic esophagitis. It emphasizes the imperative need for a continuous and combined effort from clinicians, patients, and families to promptly recognize symptoms and adaptive behavior to mitigate diagnostic delays.